Highly reflective metallic thin films for high brightness LEDs - Zheng, Bo (2018)
Improving light extraction efficiency is vital for ensuring the performance of high brightness light emitting diodes (LEDs). One of the improvement methods is to electrodeposit highly reflective silver thin films on the leadframe surfaces. Due to stricter rules and regulations, less toxic electrolytes have become more favorable in the plating industries. To date, comprehensive study on the key factors for developing highly reflective Ag films has not been widely explored. This thesis aims not only to develop low cyanide or cyanide-free electrolytes via a detailed understanding of the electrochemical science, but also to build up quantitative correlation between microstructure and reflectance of Ag films. Firstly, the literature which are relevant to the scope of this thesis are reviewed thoroughly. The recent findings, solutions and current research gap are also highlighted. Despite the increasing environmental pressure as well as health concern on the applications of cyanide, less toxic (low cyanide or cyanide free) silver plating solutions are not widely accepted in leadframe industries due to their poor light reflection performance and solution stability. Therefore, a comprehensive relationship between the microstructure of silver film and its reflectance has to be established. This review has found that more works are needed to improve the silver film reflectivity using less toxic plating solutions. The first effort starts from the Ag electroplating using a lower concentration cyanide solution (< 10g/L KCN). The electrochemical behaviors of KAg(CN)2, KCN, KNO3 electrolytes and the plating solutions pH were investigated using cyclic voltammetry for the first time. Besides that, suitable working conditions for high speed, low cyanide silver electrodeposition were also proposed. Moreover, Ag thin films were also electroplated under different current densities and their light reflection performance was determined via the reflectance measurement. The structural characteristics of these Ag films were also studied so as to correlate their influence on the films reflectance. Subsequently, a comprehensive study that correlates the effects of crystal orientation on the reflectance of silver is carried out for the first time. This can be achieved by using single crystal Ag with different crystal orientation but with controllable surface roughness. 2D (Ra) and 3D (Sdr) roughness parameters were used to characterize the surface texture of single crystal silver. It is found that surface roughness plays a more critical role in determining the reflectance while the crystal (100), (110) and (111) orientations have negligible effect on the silver reflectance. Moreover, correlations in predicting the silver reflectance by employing either 2D or 3D roughness parameters as the input variables have also been proposed. Lastly, polycrystalline silvers were used to verify the accuracy of these equations. It is observed that Sdr is a better roughness indicator in predicting the reflectance of polycrystalline silver when compared to Ra. In addition, in order to advance into developing non-cyanide system based on the aforementioned studies, the electrochemical behaviors and the effects of AgNO3, DMH, KOH, KNO3, K2HPO4 electrolytes and solutions pH on the Ag electrodeposition and dissolution were first investigated by using cyclic voltammetry. Moreover, suitable working conditions for non-cyanide silver electrodeposition were also proposed. The surface and material characteristics of Ag films deposited by non-cyanide solution were also compared with those deposited by low and high cyanide solutions as well as physical vapour deposited silver. Lastly, the research findings and goals that have been achieved are summarized. Key achievements include the development of low cyanide electroplating chemistry for high speed and highly reflective silver plating, DMH-based non-cyanide electroplating chemistry for highly reflective silver plating and statistical correlations between microstructure and reflectance of silver. This chapter also discusses the implications and limitation of this study and future opportunities such as improving the chemistry, process and performance of non-cyanide silver electroplating chemistry.